Effects of Vermicompost Inclusion on Water Quality, Feed Intake, and Growth Parameters of Nile Tilapia (Oreochromis niloticus) (Alimentos Ciencia e Ingeniería, 2024)
Fertilizing the ponds with Vermicompost did not affect the survival rate (P = 0.630) when 0, 3000, and 6000 g of fertilizer were included per pound. The final weight, the weight gain and the percentage of weight gain, the specific daily growth rate, and the feed conversion ratio were different between the fertilization treatments with 0, 3000, and 6000 g/bag of Vermicompost and ponds. The higher yields are observed when fertilized with 3000 g/bag of Vermicompost and ponds. Vermicompost fertilization does not affect water quality. The water quality, under the conditions of this study, has been classified within good quality parameters for the culture of red tilapia. In conclusion, vermicompost inclusion as a feed fertilizer for water microorganisms will serve as natural feed for the general development of Nile tilapias and contribute to promoting the production of plankton in adequate quantities. Water quality is one of the important factors for successful pond fish culture and the inclusion of vermicompost will not alter its physical-chemical parameters, allowing a fast and normal growth of this species.